Odpowiedzi

2010-02-04T19:38:49+01:00
1). 4 - 5 (3 - x) =- x - (3 - 2x)
4-15+5x=-x-3+2x
4-15+3=-5x-x+2x
-8=-4x /(-4)
x = 2

2). x - (7 + 2x) = 2 (x - 1) + 1
x-7-2x=2x-2+1
x-2x-2x=7+1
-3x=8 / (-3)
x= 8/3 = 2i2/3

3). 2x - (1 - 4x) = 2 + (8x - 5)
2x-1+4x=2+8x-5
2x+4x-8x=1+2-5
-2x=-2 / (-1)
x=1

4). 4 - 2 (5 - x) = -4 (x - 1)
4-10+2x=-4x+4
2x+4x=-4+10+4
6x=10 / 6
x = 10/6 = 1i4/6
x
  • Użytkownik Zadane
2010-02-04T19:38:59+01:00
1). 4 - 5 (3 - x) =- x - (3 - 2x)
4-15+5x=-x-3+2x
-11+5x=x-3
5x-x=-3+11
4x=8/:4
x=2

2). x - (7 + 2x) = 2 (x - 1) + 1
x-7-2x=2x-2+1
-x-7=2x-1
-x-2x=-1+7
-3x=6/:(-3)
x=-2

3). 2x - (1 - 4x) = 2 + (8x - 5)
2x-1+4x=2+8x-5
6x-1=-3+8x
6x-8x=-3+1
-2x=-2/:(-2)
x=-1

4). 4 - 2 (5 - x) = -4 (x - 1)
4-10+2x=-4x+4
-6+2x=-4x+4
2x+4x=4+6
6x=10/:6
x=10/6
x= 1 i2/3




liczę na naj(; mam nadzieje ze pomogłam ;**;)
2010-02-04T19:44:40+01:00
1) 4-15+5x=x-3+2x
5x-x-2x=-3-4+15
2x=8/:2
x=4
2) x-7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6/: -3
x=-2
3) 2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2/:-2
x=1
4) 4-10+2x=-4x+4
2x+4x=4-4+10
6x=10/:6
x=1, 2/3